Reorientation of Educational Management Strategies in Facing the Complexity of The Digital Era - Halla Azmi Tazkia; Ilham Fahmi; Muchdjabir Wahid (Journal of Educational Management Research, 2026)
The digital era has brought massive disruptions that require educational institutions to immediately reorient their management strategies in order to respond to increasingly complex global challenges. Rapid technological developments not only change learning methods but also create ambiguity in institutional governance when conventional patterns continue to be maintained. Through a qualitative literature review method, this study explores various scientific literatures and current policies to examine the paradigm shift from administrative management toward adaptive governance. The findings indicate that management strategies must urgently focus on strengthening visionary digital leadership and the flexibility of curriculum infrastructure capable of accommodating students’ personalized learning needs. In addition, improving educators’ digital pedagogical competence becomes a crucial pillar so that technology does not merely function as a tool, but as the core spirit of the learning process. This series of strategic reorientations forms the main foundation for educational institutions to transition toward collaborative and data-driven ecosystems. The courage to integrate technology holistically into organizational culture will determine the sustainability of educational quality, ensuring that institutions remain relevant, competitive, and capable of producing resilient generations amidst the uncertainties of a rapidly changing era.